REFORMULATION OF INDONESIA'S RESTORATIVE JUSTICE FRAMEWORK UNDER SUPREME COURT REGULATION NO. 1 OF 2024 - Muhammad Hanif Ramadhan; Setiawan Noerdajasakti; Faizin Sulistio (CV. RADJA PUBLIKA, 2025)
The Indonesian criminal justice system is undergoing a paradigm shift from a retributive to a restorative approach, solidified by the enactment of Supreme Court Regulation Number 1 of 2024 concerning Guidelines for Adjudicating Criminal Cases Based on Restorative Justice. This regulation aims to provide a standardized framework for judges. However, its practical implementation reveals a tension between formal legal certainty and the pursuit of substantive justice. This research conducts a normative legal analysis to evaluate the adequacy of the conditions and mechanisms within the Supreme Court Regulation as a guide for judges. The study employs statute, conceptual, and case approaches, analyzing primary and secondary legal materials. The findings indicate that the rigid requirements stipulated in the regulation, such as the limit on criminal threats, along with ambiguities in exclusionary clauses like recidivism, are insufficient and often hinder the achievement of substantive recovery. Furthermore, the absence of explicit procedural mechanisms for penal mediation forces judges to rely on discretionary activism. This journal argues for a reformulated regulation that is more flexible and principle-based, proposing the inclusion of a discretionary gateway for judges, harmonizing recidivism rules with the new National Criminal Code, and institutionalizing penal mediation procedures to ensure the restorative process is substantive and consistent.